Characterization studies on calcium silicate boards and fibre cement boards used as sheathing in light gauge steel framed systems. (May 2023) - Palagala, V.Y.; Bhanushali, J.D.; Nithyadharan, M.
Abstract: This paper presents a systematic mechanical characterization study on two types of board materials reinforced with lignocellulosic fibres used as sheathing in light gauge steel framed building, namely calcium silicate board (CSB), and fibre cement board (FCB), under tensile, compressive and shear loading. The ASTM and EN standards for wood-based panels recommend the preparation of the test specimen by bonding additional numbers of boards along thickness to eliminate global buckling under compression and shear loading. However, it is observed that the FCB and CSB specimens still suffers premature bearing failure at the loaded ends and delamination of the boards at the glued interface which often fails to characterize the actual material behaviour. To overcome this limitation, the paper proposes a unified coupon made of single (virgin) thick board and the use of combined loading compression fixtures and large panel–shear test fixtures to simulate the desired failure modes and obtain complete stress–strain response under compression and shear loading, respectively. The scope of the work majorly encompassed an extensive experimental program comprising of total 115 specimens made of FCB and CSB of thicknesses 8 mm, 10 mm and 12 mm, tested along both longitudinal and transverse directions to evaluate the constitutive properties and strength limit states. The results show that the FCB exhibits higher strength and stiffness than the CSB specimens. Further, a nonlinear stress–strain model was established to represent the response of the board material under compression.